A pilot study augmenting cognitive behavioral therapy for panic disorder with attention bias modification: Clinical and psychophysiological outcomes. (September 2020) - Baker, A.W.; Hellberg, S.N.; Jacoby, R.J.; Losiewicz, O.M.; Orr, S.; Marques, L.; Simon, N.M.
Abstract: Background and objectives: Studies show that attentional bias towards threat is a key maintenance factor for panic disorder (PD). Attentional bias may be an important mechanism of symptom reduction, and thus, a useful target for optimizing outcomes. The current study examined whether an attention bias modification (ABM) task enhanced CBT outcomes. Multiple methods for assessing PD were used, including physiological measurement and clinician-rated assessment. Methods: Adults with panic disorder (N = 24) received seven sessions of CBT with either ABM or sham attention tasks. Psychophysiological reaction to a loud tones startle paradigm was assessed before and after treatment. Results: Across both groups, panic symptom severity decreased with CBT. The ABM group showed greater reductions in PD symptoms compared to the placebo group. Notably, however, changes in attentional bias were not associated with symptom reductions across groups. No significant group differences on psychophysiological assessment were observed. Limitations: This study is limited by the small sample size, which rendered our power to investigate mediators and moderators insufficient. More research is needed to validate the effect of attention bias modification on attentional bias to threat. Conclusions: This pilot study suggests that future research should investigate attentional bias in conjunction with CBT. A larger sample would provide opportunity to further investigate the mechanisms through which ABM works, along with potential moderating factors and the use of psychophysiological measurements in panic disorder. Highlights: Attention bias modification (ABM) enhanced CBT for panic disorder (PD). Contrary to hypotheses, ABM did not significantly reduce attention bias scores. Pre-to post-treatment changes in attention bias and panic symptoms were uncorrelated. Across groups, response was associated with larger declines in resting heart rate. Further research on efficacy and mechanisms of ABM and CBT for PD is indicated.